Creating a Selective Nanobody Against 3-Nitrotyrosine Containing Proteins - Van Fossen, Elise M.; Grutzius, Sonia; Ruby, Carl E.; Mourich, Dan V.; Cebra, Chris; Bracha, Shay; Karplus, P. Andrew; Cooley, Richard B.; Mehl, Ryan A. (Frontiers in Chemistry, 2022)
A critical step in developing therapeutics for oxidative stress-related pathologies is the ability to determine which specific modified protein species are innocuous by-products of pathology, and which are causative agents. To achieve this goal, technologies are needed that can identify, characterize, and quantify oxidative post translational modifications (oxPTMs). Nanobodies (Nbs), represent exquisite tools for intracellular tracking of molecules due to their small size, stability and engineerability. Here, we demonstrate that it is possible to develop a selective Nb against an oxPTM protein, with the key advance being the use of genetic code expansion (GCE) to provide an efficient source of the large quantities of high-quality, homogenous, and site-specific oxPTM-containing protein needed for the Nb selection process. In this proof-of-concept study, we produce a Nb selective for a 3-nitrotyrosine (nitroTyr) modified form of the 14-3-3 signaling protein with a lesser recognition of nitroTyr in other protein contexts. This advance opens the door to the GCE-facilitated development of other anti-PTM Nbs.